2018
DOI: 10.1177/2326409818779097
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic Stem Cell Transplantation in Mucopolysaccharidosis Type II

Abstract: Mucopolysaccharidosis II (MPS II-Hunter syndrome) is an X-linked lysosomal storage disorder caused by a deficiency in iduronate-2 sulfatase. Enzyme replacement therapy does not cross the blood-brain barrier (BBB), limiting the results in neurological forms of the disease. Another treatment option for MPS, hematopoietic stem cell transplantation (HSCT) has become the treatment of choice for the severe form of MPS I since it can preserve neurocognition when performed early in the course of the disease. Even thou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 45 publications
0
19
0
1
Order By: Relevance
“…HSCT was applied for the first time for MPS II in 1986 to a 7 year old patient [145]; even if the intellectual ability was stabilized after transplantation, the plasma enzyme levels remained far below normal and 3.5 years after transplantation, the patient died due to cardiovascular complications [146].…”
Section: Haematopoietic Stem Cell Transplantation (Hsct)mentioning
confidence: 99%
See 1 more Smart Citation
“…HSCT was applied for the first time for MPS II in 1986 to a 7 year old patient [145]; even if the intellectual ability was stabilized after transplantation, the plasma enzyme levels remained far below normal and 3.5 years after transplantation, the patient died due to cardiovascular complications [146].…”
Section: Haematopoietic Stem Cell Transplantation (Hsct)mentioning
confidence: 99%
“…Therefore, the clinical experience with HSCT in MPS II is small, especially compared to MPS I, for which more than 600 transplantations have been performed. Available data on HSCT in MPS II are outdated or reveal poor patient selection criteria (especially concerning the presence of neurological symptoms and the age at transplantation) and a great variability of cell sources, conditioning regimens, and outcomes of interest [146]. A study performed by Tanaka and colleagues, evaluating the long effects of HSCT, showed an improvement in uGAG levels, heart valve regurgitation, brain magnetic resonance imaging (MRI) atrophy, category I and II brain lesions, and activity of daily living (ADL).…”
Section: Haematopoietic Stem Cell Transplantation (Hsct)mentioning
confidence: 99%
“…However, these recommendations have a higher degree of evidence than the individual beliefs of a single investigator; and they had a great utility summarizing the available knowledge to guide clinical practice and the future investigations (Scarpa et al, 2011;Barth and Horovitz, 2018). Nowadays, HSCT is reconsidered as therapy in other forms of neuronopathic MPS after the development of new treatment techniques and the creation of umbilical cords bank and bone marrow donor registries (Barth and Horovitz, 2018). Accordingly, the Cochrane guidelines accept the inclusion of nonrandomized study designs in systematic reviews under some constraints: "i) when randomized trials are unable to address the effects of the intervention on harm and long-term outcomes or in specific populations or settings; or ii) for interventions that cannot be randomized (e.g., policy change introduced in a single or small number of jurisdictions)" (Higgins et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Experience with HSCT in MPS II is limited, but recent studies have demonstrated some efficacy in terms of reducing GAG levels, and improving some of the somatic manifestations such as coarse facial features, joint stiffness, hearing defects, hernia, hepatosplenomegaly and heart valve disorders. In addition, improvements in activities of daily living and the frequency of respiratory infections have also been reported 2,27–30 . There is also preliminary evidence of modest neurological benefit with HSCT in MPS II patients, which has not been evident with ERT 28,29 …”
Section: Mucopolysaccharidoses: a Rare And Heterogeneous Group Of Mulmentioning
confidence: 98%
“…In addition, improvements in activities of daily living and the frequency of respiratory infections have also been reported 2,27–30 . There is also preliminary evidence of modest neurological benefit with HSCT in MPS II patients, which has not been evident with ERT 28,29 …”
Section: Mucopolysaccharidoses: a Rare And Heterogeneous Group Of Mulmentioning
confidence: 98%